1999
DOI: 10.1016/s0014-5793(99)00990-4
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan mediated photoreduction of disulfide bond causes unusual fluorescence behaviour of Fusarium solani pisi cutinase

Abstract: The fluorescence signal of the single tryptophan residue (Trp 69 ) of Fusarium solani pisi cutinase is highly quenched. However, prolonged irradiation of the enzyme in the tryptophan absorption band causes an increase of the tryptophan fluorescence quantum yield by an order of magnitude. By using a combination of NMR spectroscopy and chemical detection of free thiol groups with a sulfhydryl reagent we could unambiguously show that the unusual fluorescence behaviour of Trp 69 in cutinase is caused by the breaki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
65
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 32 publications
9
65
1
Order By: Relevance
“…Disulphide bridges are known to be excellent quenchers of excited-state aromatic residues. However, selective prolonged irradiation of the Trp residue at 295 nm increases its fluorescence quantum yield, in agreement with previous results by Weisenborn et al (1996) and Prompers et al (1999). It was also observed that on irradiation of cutinase with light at 295 nm, free thiol groups are present in cutinase (see Fig.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Disulphide bridges are known to be excellent quenchers of excited-state aromatic residues. However, selective prolonged irradiation of the Trp residue at 295 nm increases its fluorescence quantum yield, in agreement with previous results by Weisenborn et al (1996) and Prompers et al (1999). It was also observed that on irradiation of cutinase with light at 295 nm, free thiol groups are present in cutinase (see Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Because Prompers et al (1999) reported none of the above parameters on which p depends, we can not compare their findings with ours. Also, the concentration of protein used by Prompers et al (500 M cutinase solution) is drastically higher then ours (2, 4, 14, and 17 M), making comparison impossible.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations